TO MEMORY OF SOULPASTOR EVSTAHY MATSKIV - Макаровський, І. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Ideological direction of life and activity soulpastor Evstahiy Matskiv is lighted in the article.